Morphology of the immune cells in the wall of the human uterine tube and their possible impact on reproduction—uterine tube as a possible immune privileged organ - Visnyaiová, Kristína; Varga, Ivan; Feitscherová, Claudia; Pavlíková, Lada; Záhumenský, Jozef; Mikušová, Renáta (Frontiers in Cell and Developmental Biology, 2024)
The uterine tube, as well as other parts of the upper female reproductive system, is immunologically unique in its requirements for tolerance to allogenic sperm and semi-allogenic embryos, yet responds to an array of sexually transmitted pathogens. To understand this dichotomy, there is a need to understand the functional morphology of immune cells in the wall of the uterine tube. Thus, we reviewed scientific literature regarding immune cells and the human uterine tube by using the scientific databases. The human uterine tube has a diverse population of immunocompetent cells representing both the innate and adaptive immune systems. We describe in detail the possible roles of cells of the mononuclear phagocyte system (macrophages and dendritic cells), T and B lymphocytes, NK cells, neutrophils and mast cells in association with the reproductive functions of uterine tubes. We are also discussing about the possible "immune privilege" of the uterine tube, as another mechanism to tolerate sperm and embryo without eliciting an inflammatory immune response. In uterine tube is not present an anatomical blood-tissue barrier between antigens and circulation. However, the immune cells of the uterine tube probably represent a type of "immunological barrier", which probably includes the uterine tube among the immunologically privileged organs. Understanding how immune cells in the female reproductive tract play roles in reproduction is essential to understand not only the mechanisms of gamete transport and fertilization as well as embryo transport through the uterine tube, but also in improving results from assisted reproduction.